1979
DOI: 10.1007/bf00236998
|View full text |Cite
|
Sign up to set email alerts
|

Cellular organization of the lateral and postinfundibular regions of the median eminence in the rat

Abstract: The structural organization of the rostral, lateral and postinfundibular regions of the median eminence (ME) of 5-day cyclic diestrous rats was studied with light and electron microscopic methods. The ependymal cells lining (i) the floor of the infundibular recess (IR) at rostral levels, (ii) the lateral extensions of the IR, and (iii) the floor of the premammillary recess appear to represent the same type of tanycyte ependyma (beta 1 tanycytes). In the entire width of the rostral and postinfundibular palisade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
0
2

Year Published

1982
1982
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 43 publications
7
97
0
2
Order By: Relevance
“…2 E and F, arrows). This corresponds to the known distribution of ependymal tanycytes (24,25), a specialized population of glial cells implicated in the transport of hormones, and other substances in the hypothalamus (26). The relative amounts of D2 mRNA in the hypothalamus and layers 1-4 of the parietal cortex were compared by measuring the optical density of these regions on a lowexposure autoradiograph (Fig.…”
Section: Resultssupporting
confidence: 54%
“…2 E and F, arrows). This corresponds to the known distribution of ependymal tanycytes (24,25), a specialized population of glial cells implicated in the transport of hormones, and other substances in the hypothalamus (26). The relative amounts of D2 mRNA in the hypothalamus and layers 1-4 of the parietal cortex were compared by measuring the optical density of these regions on a lowexposure autoradiograph (Fig.…”
Section: Resultssupporting
confidence: 54%
“…The appearance of DII mRNA in the ependymal zone and the ME (6) together with our recent observation of glial fibrillary acidic protein in cells expressing DII mRNA (29) and a previous report (30) on the expression of DII in glial cells in neonatal rat brain strongly indicate that DII-producing cells are astrocytes and tanycytes. These glial cells provide an extensive network of cellular processes in the ARC (31)(32)(33)(34) and suggest a paracrine action on PVN-projective ARC neurons via the production of thyroid hormones. In our previous study (29), we have shown that neurons in the ARC heavily project to neuroendocrine TRH cells in the PVN, and we recently found that a robust NPY innervation of TRH cells (35) originates from the ARC (36).…”
Section: Discussionmentioning
confidence: 99%
“…l-pm thick serial sections were obtained of the whole ME-PT (about 2 mm long), from the cephalic end up to the caudal end (pituitary stalk). Every 100 um a few ultrathin sections of the ME-PT were obtained [31]. Thus, ultrathin frontal sections were obtained from 20 different lev els in the cephalic-caudal direction.…”
Section: Immunocytochemistrymentioning
confidence: 99%